The Model Pembelajaran Bahasa Jawa Berbasis Proyek dalam Kurikulum Merdeka - Verrysaputro, Exwan Andriyan; Subekti, Panca Aditya (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
The purpose of this research is to present the implementation of a project-based learning model in Javanese language subjects. Descriptive qualitative method is used as the procedural steps in this research. Data in the research are collected through interview techniques, observations, and documentation. The data analysis technique used is Miles and Huberman's, which involves the steps of 1) data collection, 2) data reduction, 3) data presentation, and 4) data conclusion. Informants include the school principal, teachers, and students. The results of this research show that the project-based learning model is implemented for the wayang (traditional Javanese puppet) material. The findings indicate that the Project-Based Learning Model is very suitable as an alternative Javanese language learning model in the Merdeka Curriculum. This Project-Based Learning Model for Javanese language is implemented by preparing students of class VII F, arranging activity schedules, supervising the implementation, assessing students, and conducting evaluations.